PENGEMBANGAN MEDIA VIDEO TUTORIAL UNTUK PEMBELAJARAN PRAKARYA SUB MATERI KERAJINAN MAKRAME DI KELAS VII SEKOLAH MENENGAH PERTAMA - Dian Masitha Ulfa; Ramalis Hakim (Universitas Negeri Padang, 2020)
This study aims to find the results of the level ov validity, practicallity and efectiveness of the product in the form of a video tutorial media for learning the craft sub subject of macrame craft in junior high schools. This study uses the R&D or research and development with 4D model. Subject trial involving three validators are validators media, material and language.The media trial subjects were 20 students and one teacher of craft subject. This study uses data analysistechniques namely quantitative and qualitative descriptive analysis. Data collection methods are intervies, documentation, and questionners. The results of this study stated that the media that authors develop were declared valid, effective and practically used in learning crafts.